2010
DOI: 10.1038/cmi.2010.47
|View full text |Cite
|
Sign up to set email alerts
|

Identification of p100 target promoters by chromatin immunoprecipitation-guided ligation and selection (ChIP-GLAS)

Abstract: The multifunctional protein p100 is a vital transcriptional regulator that increases gene transcription by forming a physical bridge between promoter-specific transcription factors and the basal transcription machinery. To identify potential signal transduction pathways in which human p100 acts as a coregulator and to find target promoter regions that may interact with p100, we performed a promoter microarray assay called chromatin immunoprecipitation-guided ligation and selection (ChIP-GLAS). From this assay,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…It was also reported that SND1 could interact with astrocyte elevated gene-1 (AEG-1) in breast cancer and strongly promote lung metastasis (12). In our earlier work using chromatin immunoprecipitation guided ligation and selection (ChIP-GLAS) assays, we have demonstrated that SND1 is potentially involved in the TGFb signaling pathway in breast cancer cells (13). However, it remains unclear how SND1 is upregulated in breast cancer and how SND1 participates in breast cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that SND1 could interact with astrocyte elevated gene-1 (AEG-1) in breast cancer and strongly promote lung metastasis (12). In our earlier work using chromatin immunoprecipitation guided ligation and selection (ChIP-GLAS) assays, we have demonstrated that SND1 is potentially involved in the TGFb signaling pathway in breast cancer cells (13). However, it remains unclear how SND1 is upregulated in breast cancer and how SND1 participates in breast cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in a breast cancer model, SND1 is required for the expansion and activity of tumor-initiating cells (16). We also reported earlier that SND1 can form a loop with SMAD family members and reciprocally regulate the promotion of breast cancer metastasis through a TGF-b-signaling pathway (17)(18)(19). As a multifunctional protein, it is likely that SND1 regulates diverse signal pathways involved in proliferation and metastasis in different cancers (20,21).…”
mentioning
confidence: 59%
“…In support of our data, Arretxe et al (25) showed that SND1 was potentially able to recognize the promoter region of SLUG through ChIP-on-chip assays. In our previous study, we likewise found that SLUG is a target promoter of SND1 by ChIP-guided ligation and selection assay (17). We therefore performed experiments to discover the potential role of SND1 in regulating the gene transcriptional activation of SLUG, which further affects the expression of epithelial markers.…”
Section: Snd1 Activates Slug Transcription By Increasing Chromatin Acmentioning
confidence: 86%
“…23 This domain has been reported to recognize and bind methylated lysine and arginine of target proteins, which is a key factor for their ability to facilitate the assembly of larger protein complexes at discrete cellular compartments. [24][25][26][27][28][29] It seems that a common function of proteins containing Tudor domain, including TSN, is to act as an adaptor in order to link methylated arginine or lysine to effector molecules with specific catalytic activities. 24 It has recently been shown that human TSN interacts through its Tudor domain with core components of RNA splicing machinery, including Prp8 (human U5-220 kD Protein), two Sm proteins, SmB and SmD1/D3 and the splicing factor SAM68 (Src-associated in mitosis of 68 kDa).…”
Section: Structure and Intracellular Localization Of Tsn: Clues To Mumentioning
confidence: 99%
“…6,7 Accordingly, a set of TSN-bound promoter regions has been recently identified using chromatin immunoprecipitation. 26 The interaction of TSN with multiple components of transcription machinery makes it an important factor in the regulation of a plethora of cellular signaling pathways implicated in the pathogenesis of various human diseases.…”
Section: Structure and Intracellular Localization Of Tsn: Clues To Mumentioning
confidence: 99%